Impact of an Exercise Protocol on Sexuality and Quality of Life of Climacteric Women - Amaral, Maria Teresa Pace do; Scudeller, Tânia Terezinha; Santos, Marcella Carvalho Franco dos; Guidorzi, Natalia Vidal; Zanetti, Miriam Raquel Diniz (ABCS Health Sciences, 2020)
Introduction: Climacteric is a period of transition between the reproductive and non-reproductive phases of the woman, due to hypoestrogenism. Some symptoms such as vasomotor and urogenital disorders and sexual dysfunctions are characteristics of this period that can interfere negatively in women´s quality of life. However, specific exercises can positively influence the improvement of these conditions. Objective: To verify the impact of a physiotherapist supervised exercise protocol on menopausal symptoms, sexuality and quality of life of climacteric women. Methods: A descriptive study with physiotherapeutic intervention through a specific exercise protocol. Participated in the study 18 women attended to Instituto da Mulher e Gestante, in the city of Santos (SP). Results: The women underwent initial physiotherapeutic evaluation, answered the Sexuality Questionnaire Female Sexual Function Index, Kupperman Menopausal Index and SF-36 quality of life. They were then submitted to health education about climacteric period and also to a physiotherapist supervised exercise group, once a week, lasting 50 minutes, for 12 weeks. The same questionnaires were reapplied at the end of this period. Conclusion: The protocol of specific group exercises supervised by physiotherapist did not influence sexual function, but it was effective for better quality of life and decreased significantly climacteric symptomatology.